Digital Comics as a Learning Media for Local History in Senior High Schools - Kasih, Imamah Candra; Firmansyah, Andang; Putri, Astrini Eka; Nudiati, Deti (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
This research intends to create educational materials through digital comics centered on local history and assess their usability for 10th graders in senior high school. The study utilized the Research and Development (R & D) approach, following the ADDIE model. The participants included 10th-grade students, and assessments were carried out by both material and media specialists. Data collection methods consisted of direct observations, interviews, surveys, and evaluations from experts. The analysis of the data was performed using a descriptive method, incorporating both qualitative and quantitative techniques by means of scoring and student feedback.The findings reveal that the digital comics focusing on local history achieved a “highly feasible” rating from material specialists, media specialists, and subject teachers, along with favorable feedback from students. The evaluation by media experts showed a score of 94. 17% (highly feasible), the validation from material specialists was 86. 75% (highly feasible), while subject teachers gave a perfect score of 100% (highly feasible). In addition, the pilot test with a small group received a score of 74%, while the larger group trial scored 77%, both of which are deemed suitable. Therefore, the digital comics on local history are judged appropriate and hold potential as an alternative educational resource for history classes.